Integration of biomechanical and developmental concepts in the acquisition of throwing: effects on developmental characteristics and gender differences - Stodden, D. F.; Rudisill, M. E. (Journal of Human Movement Studies, 2006)
The purpose of this study was to assess the effectiveness of throwing instructional strategy, which integrated biomechanical and developmental concepts, on developmental performance characteristics and gender differences as compared to the effectiveness of a traditional throwing instructional strategy. 33 kindergarten children participated in a four-week study with six instructional sessions. A 2 x 2x2 (gender x treatment x time) mixed-design MANOVA was used to determine the effect of thce independent variables on five dependent throwing measures (stepping action. trunk action, humerus action, forcarm action, and ball velocity). The MANOVA results indicated there was an overall main effect for treatment among all participants. F(1.29)=5.60, p=0.025 although there was no significant main effect for treatment between groups, F(1.29)=2.12, p=0.156. Results also showed a significant three-way (gender x treatment x time) interaction which indicated that females and males responded differentally to instruction. These results suggest the instructional strategy integrating biomechanical and developmental concepts was more effective in promoting certain aspects of throwing skill. This instructional protocol also is the first study to show a reduction in gender differences in throwing arm components.